2021
DOI: 10.1126/science.abi7687
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh energy storage in superparaelectric relaxor ferroelectrics

Abstract: Minimal domains for maximum energy Dielectric capacitors are important electronic components that can store energy, at least for a short period of time. Pan et al . used phase-field simulations to help determine the right combination of bismuth iron oxide, barium titanium oxide, and samarium doping that is likely to generate a material with excellent dielectric properties (see the Perspective by Chu). The simulations guide a set of experimental measurements showin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
242
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 386 publications
(275 citation statements)
references
References 44 publications
5
242
1
1
Order By: Relevance
“…Recently, a series of promising data have been reported [32][33][34][35][36]. Using a superparaelectric design, Pan et al achieved very high recoverable energy density (J rec = 152 J/cm 3 ) in BiFeO 3 -BaTiO 3 -based RFE thin films [21,37,38]. By means of Sr doping, Acharya et al reported ultrahigh energy efficiency (η = 97%) in AFE Pb 1-x Sr x HfO 3 thin films [39], where the J rec and E B were 77 J/cm 3 and 5.12 MV/cm, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a series of promising data have been reported [32][33][34][35][36]. Using a superparaelectric design, Pan et al achieved very high recoverable energy density (J rec = 152 J/cm 3 ) in BiFeO 3 -BaTiO 3 -based RFE thin films [21,37,38]. By means of Sr doping, Acharya et al reported ultrahigh energy efficiency (η = 97%) in AFE Pb 1-x Sr x HfO 3 thin films [39], where the J rec and E B were 77 J/cm 3 and 5.12 MV/cm, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, AFE-based materials have been proposed to design memory dev In recent years, both AFE-based and relaxor FE (RFE)-based capacitors [21][22][23][24][25][26] widely investigated due to their reducible energy loss [22,27], improvable polarization (Pmax), breakdown electric field (EB) [28][29][30] and energy efficiency Recently, a series of promising data have been reported [32][33][34][35][36]. Using a super design, Pan et al achieved very high recoverable energy density (Jrec = 152 J/cm 3 BaTiO3-based RFE thin films [21,37,38]. By means of Sr doping, Acharya et a ultrahigh energy efficiency (η = 97%) in AFE Pb1-xSrxHfO3 thin films [39], where EB were 77 J/cm 3 and 5.12 MV/cm, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…12). 7,[22][23][24][25][26][27][28][29][30][31][32][33][34] Of particular importance is the observation that despite being thick and polycrystalline form, our PZT lms exhibited the same E DBS level as that of thin epitaxial as well as domain-engineered lms and outperformed the polycrystalline lms with thickness above 1 µm. Thus, the nanograin engineered thick lms meet the standard of practical applications requiring a high energy level due to their high voltage (over 1000 V) endurance capacity and easy fabrication route.…”
Section: Electrical and Energy Storage Properties Of Nanograin-engine...mentioning
confidence: 99%
“…3d). 7,[22][23][24][25][26][27][28][29][30][31][32][33][34] Reliability evaluation and charging-discharging performance of nanograin-engineered RFE PZT thick lm capacitors…”
Section: Electrical and Energy Storage Properties Of Nanograin-engine...mentioning
confidence: 99%
“…[1][2][3] However, the energy storage densities of dielectric capacitors are relatively low, which has stimulated substantial efforts to seek possible approaches to improve the energy capability of the dielectric capacitors with functional integration and miniaturization. [4][5][6] In the last few decades, relaxor ferroelectric (RFE) thin lm dielectrics have been demonstrated to exhibit both high energy efficiency and a large breakdown strength due to the delayed polarization switching under an electric eld, showing superior energy storage performance compared to the ferroelectrics and linear dielectrics. 7,8 These properties have commonly been ascribed to the polar nanoregions present in RFEs, which are proposed to be gradually switched and aligned to the electric eld due to the lower energy barrier between the intercoupled nanodomains.…”
Section: Introductionmentioning
confidence: 99%